ICT Interventions for Improved Health Service Quality and Delivery in India: A Literature Review - Manisha Wadhwa (Columbia University, Earth Institute, Center for Sustainable Development (CSD), 2019)
Over the last few decades, the Information and Communication Technology (ICT) has revolutionized the way the healthcare is delivered in India. ICT acts as a catalyst for speedy delivery of healthcare services. It is now possible to connect healthcare delivery in rural areas to the mainstream. ICT has made a valuable contribution to healthcare decision making. This is a concept paper based on secondary data collected from government documents and websites, various national and international Journals and private websites. The present paper discusses potential effects and application areas of ICT in health, existing and emerging ICT based platforms, e-Health policies and strategies and current challenges in ICT implementation specific to scenario in India. This document lays specific emphasis on the role of ICT in improving healthcare service delivery at India's sub-centre level. This paper also presents a review of evidence base from International studies related to how ICT interventions can improve health service quality and delivery. The use of the Information and Communication Technology (ICT) in Health is defined as e-Health. It encompasses broader concepts like m-Health, telemedicine, Health Information Systems, electronic health records and many more. Each of the ICT intervention has brought its own bundle of benefits to healthcare. Mobile Technology is being used for the purposes of data collection, health workforce training, early warning of unusual health related events and many more. With the advancement of Telemedicine and Tele-counselling, it is now possible to deliver health care services in rural and remote areas of the country. Health information systems have made possible the monitoring of health data in real time. Electronic health records (EHRs) have made it possible to digitize paper health records and has made healthcare delivery quick, coordinated, transparent and secure. (...)
Keywords: 330; Information and Communication Technology; ICT; e-Health; m-Health; India